(untitled) (Quinto Sol, 2014)
If we focus on the educational field, which is the one we are more interested in, we can see that Roca, during his second presidency, tries to make a drastic change in the public educational system in order to eliminate the exclusively political function of the education and create another system following Alberdian postulates.